Democracy, Human Rights and Islamic Law in Mohammed Abed Al-Jabiri’s Reformist Ideas - Adrian, Muhammad Fikri (Universitas Islam Indonesia, 2024)
Mohammed Abed Al-Jabiri, an influential reformist Muslim thinker from Morocco, offers critical reading of the challenges of modernity and the role of religion in dealing with these challenges. This study aims to explore and present some of al-Jabiri's reformist ideas on contemporary issues that are expected to contribute to the literature of contemporary Islamic thought. This study employs the content analysis method. The analysis begins with a discussion of the relationship between religion and the state, then continues with the issue of the application of Islamic law, then the issue of democracy, and ends with a discussion of the issue of human rights. The study also compares al-Jabiri's thoughts with those of other Muslim thinkers such as Rachid Ghannaouchi, Malik Bennabi, Azyumardi Azra, and others. The results of this study reveal several main points. On the relationship between religion and the state, Al-Jabiri argues that Islam provides freedom for its people to do ijtihad to determine the ideology that is most relevant to their needs. Regarding the application of Islamic law, al-Jabiri offers two methods that he considers to be responsive to the need for legal certainty: the first method is the universality of law and the second is maqasid al-sharia which prioritizes the public good. As for democracy and human rights, al-Jabiri tries to define and harmonize the two ideas with Islam.